Ongediertes : a critical qualitative study of farmer–black-backed jackal conflict and its management around the Square Kilometre Array core site in the Northern Cape, South Africa - Terblanche, Renelle (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.